Levels of mRNA coding for motoneuron growth-promoting factors are increased in denervated muscle. - Rassendren, F A (1992)
Partial denervation of skeletal muscle induces sprouting of axons remaining within the muscle, possibly as a result of increased synthesis by denervated muscle fibers of motoneuron growth-promoting factors. Direct verification of this hypothesis has not been possible because the molecules responsible are not unambiguously characterized. We used Xenopus oocytes as a functional assay for mRNAs coding for secreted growth factors: preparations of mRNA from innervated and denervated neonatal muscle were injected into oocytes. Three days later, oocytes injected with denervated muscle mRNA expressed increased levels of nicotinic acetylcholine receptor and voltage-dependent sodium channels at their membrane. Proteins secreted by the same oocytes were tested for their effects on (i) neurite outgrowth from embryonic chicken ventral spinal cord neurons; (ii) survival in mixed culture of embryonic chicken motoneurons identified using the SC1 antibody; and (iii) survival of embryonic motoneurons purified by panning on SC1 antibody. In all three assays, media conditioned by oocytes injected with mRNA from denervated muscle contained significantly higher levels of biological activity than did those from oocytes injected with innervated muscle mRNA or water. mRNA was prepared from muscle at different times after denervation: a maximal increase was obtained already after 1 day, consistent with an involvement in sprouting. Synthesis of motoneuron growth-promoting factors is thus regulated by denervation in a parallel fashion to that of other key components of the neuromuscular junction.